2001
DOI: 10.1099/0022-1317-50-9-759
|View full text |Cite
|
Sign up to set email alerts
|

An in-vitro model for studying the interaction of Escherichia coli O157:H7 and other enteropathogens with bovine primary cell cultures

Abstract: Sections of kidney, trachea, ileum, colon, rectum and rumen were removed at post mortem from a neonatal calf and, with the exception of the rumen, primary cell lines were established for each of the cell types. The adherence of enterohaemorrhagic Escherichia coli (EHEC) serotype O157:H7, enteropathogenic E. coli (EPEC) serotype O111, E. coli K12 (a laboratory adapted non-pathogenic strain) and Salmonella enterica serotype Typhimurium was assayed on each cell type. For all adherence assays on all cell lines, EH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 15 publications
2
36
0
Order By: Relevance
“…The cells were derived following the adaptation of an enzymatic digestion approach (Dibb-Fuller et al, 2001;Föllmann et al, 2000) coupled to a mechanical dissection, which had been previously successful in yielding primocultures of both jejunocytes and colonocytes from adult cattle (Rusu et al, 2005). Immortalization was achieved by transfection with the tumour large T antigen of the simian leukaemia virus 40 (SV40 LT).…”
Section: Introductionmentioning
confidence: 99%
“…The cells were derived following the adaptation of an enzymatic digestion approach (Dibb-Fuller et al, 2001;Föllmann et al, 2000) coupled to a mechanical dissection, which had been previously successful in yielding primocultures of both jejunocytes and colonocytes from adult cattle (Rusu et al, 2005). Immortalization was achieved by transfection with the tumour large T antigen of the simian leukaemia virus 40 (SV40 LT).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that specific type III effector molecules are required for the formation of classic attaching and effacing lesions in calves (Cookson and Woodward 2003); however, not all colonization is associated with the formation of actin pedestals (Vlisidou et al 2006). In addition, EHEC O157:H7 actin pedestals do not have the same appearance in cattle as those in disease-susceptible animals (Dibb-Fuller et al 2001), and a recent study suggests that this is attributable to lower expression of type III effector molecules in cattle (Rashid et al 2006). In contrast, Rashid et al (2006) determined that Shiga toxin expression is not different for human and cattle systems suggesting that cytotoxins could play a similar role in both systems.…”
mentioning
confidence: 68%
“…E. coli O157:H7 strain NCTC12900, a well-characterized Shiga toxin-negative EHEC strain of human origin (15), was used for experimental infections in calves. We used this Shiga toxin-negative strain for biosafety reasons.…”
Section: Methodsmentioning
confidence: 99%